2012
DOI: 10.1002/cmmi.500
|View full text |Cite
|
Sign up to set email alerts
|

Impact of H‐aggregation on activatable MMP‐2‐specific probes for optical imaging

Abstract: In order to target and image MMP-2 activity using optical imaging, we developed a panel of new MMP-2 probes based on Cy5 and QSY21 as fluorophore/quencher FRET partners, separated by various MMP-2 specific peptide substrates. We compared these probes for their specificity against other MMPs, their rate of activation by MMP-2 and their initial quenching.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…Given the high concentration and size of albumin, the authors suggested that the probe would be largely bound to albumin and this interaction would therefore define the kinetics of their probe by causing unspecific accumulation through the EPR effect. We also reported on how albumin binding by some fluorescent probes may affect their optical properties . Hence, special care should be taken to assess unspecific protein binding of novel probes and its effect on accumulation and signal.…”
Section: Controls In Molecular Imagingmentioning
confidence: 99%
See 4 more Smart Citations
“…Given the high concentration and size of albumin, the authors suggested that the probe would be largely bound to albumin and this interaction would therefore define the kinetics of their probe by causing unspecific accumulation through the EPR effect. We also reported on how albumin binding by some fluorescent probes may affect their optical properties . Hence, special care should be taken to assess unspecific protein binding of novel probes and its effect on accumulation and signal.…”
Section: Controls In Molecular Imagingmentioning
confidence: 99%
“…. Our group also recently published a set of Cy5/QSY21 MMP‐2 targeting agents . These smaller molecules are likely to penetrate more easily into tissues, but will be eliminated more quickly than most FF probes.…”
Section: Imaging Modalities and Probe Designsmentioning
confidence: 99%
See 3 more Smart Citations